Evolution of hematological parameters and death in patients with COVID-19 in a hospital in Paraguay, 2021 - Santacruz, Lorena; Samudio, Margarita; Mereles Aranda, Eva Fabiana; Vargas Correa, Arturo; Poullion, Daniela; Santacruz, Gabriela; Ojeda, Leticia; Fretes, Doria; Villalba, Blanca (Medicina Clínica y Social, 2024)
Introduction: Hematological parameters provide the medical team with useful prognostic markers in the clinical evolution of COVID-19 disease. The objective was to analyze the relationship between the unfavorable evolution of hematological values and the death of patients hospitalized with COVID-19. Methodology: The study is observational, correlational, and longitudinal. A review of the clinical records of patients over 18 years of age hospitalized between January and March 2021 was carried out. The results of the hematological parameters at admission, at 48 hours, at 8 days and at discharge were recorded in an Excel spreadsheet. The data were analyzed with Epi Info 7.1 (CDC, Atlanta) according to descriptive statistics. Results: Of 144 patients, 68 (47.2%) deaths were observed, with a predominance of males (63.2%) and those over 60 years of age (47.1%). The factors associated with mortality were hypertension (52.9% vs 31.6%; p=0.009), diabetes (50% vs 26.3%; p=0.003) and obesity (41.2% vs 25 %; p=0.039). The unfavorable hematological parameters associated with mortality occurred after 8 days of hospitalization with leukocytosis (64.1% vs 33.3%; p=0.003), lymphopenia (96.8% vs 79%; p=0.008), neutrophilia (98.5% vs 87.7%; p=0.029) and a high neutrophil/lymphocyte ratio (NLR) (96.9% vs 75.4%; p=0.001). Discussion: The hematological parameters that were associated with mortality were leukocytosis with neutrophilia, lymphopenia, and elevated NLR. These parameters could have prognostic value in follow-up to contribute to the management of these patients.